Application of Organoids in Carcinogenesis Modeling and Tumor Vaccination - Wang, Zeyu; Zhao, Shasha; Lin, Xiaolin; Chen, Guanglong; Kang, Jiawei; Ma, Zhongping; Wang, Yiming; Li, Zhi; Xiao, Xiuying; He, Aina; Xiang, Dongxi (Frontiers in Oncology, 2022)
Organoids well recapitulate organ-specific functions from their tissue of origin and remain fundamental aspects of organogenesis. Organoids are widely applied in biomedical research, drug discovery, and regenerative medicine. There are various cultivated organoid systems induced by adult stem cells and pluripotent stem cells, or directly derived from primary tissues. Researchers have drawn inspiration by combination of organoid technology and tissue engineering to produce organoids with more physiological relevance and suitable for translational medicine. This review describes the value of applying organoids for tumorigenesis modeling and tumor vaccination. We summarize the application of organoids in tumor precision medicine. Extant challenges that need to be conquered to make this technology be more feasible and precise are discussed.